2017
DOI: 10.1002/pri.1702
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and circumstances of falls for people with Charcot–Marie–Tooth disease: A cross sectional survey

Abstract: The impact of falls is far reaching, in terms of injury risk and the consequences of the fear of falling. Interventions to improve balance and reduce falls are an important rehabilitation focus for people with CMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Tripping was the most common mechanism of falls in children with CMT, likely due to ankle dorsiflexor weakness with associated footdrop, consistent with other reports of frequent trips and falls across the lifespan 5 15. While only two children wore ankle foot orthotics (AFOs), gait analysis of children with CMT has previously suggested that AFOs may assist those with foot drop in swing phase of gait,30 thus reducing the risk of tripping.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Tripping was the most common mechanism of falls in children with CMT, likely due to ankle dorsiflexor weakness with associated footdrop, consistent with other reports of frequent trips and falls across the lifespan 5 15. While only two children wore ankle foot orthotics (AFOs), gait analysis of children with CMT has previously suggested that AFOs may assist those with foot drop in swing phase of gait,30 thus reducing the risk of tripping.…”
Section: Discussionsupporting
confidence: 80%
“…Two studies of adults with neuromuscular disease have reported falls; in 27% of participants over 3 months13 and 61% over 6 months,14 with leg weakness and poor balance associated with increased falls risk 13 14. In a further study, nearly 50% of adults with CMT reported falling at least once a month 15…”
Section: Introductionmentioning
confidence: 98%
“…While postural control performance in laboratory or clinical settings mimics real‐world conditions, it is imperfect, particularly with regard to balance. Experience in adult CMT studies suggests that proactive and reactive balance strategies must be explored further, and outcome measures should reflect real‐life circumstances when evaluating falls . Additionally, balance confidence will influence how an individual approaches challenging environments, fall frequency, and their overall participation .…”
Section: Acknowledgmentmentioning
confidence: 99%
“…Experience in adult CMT studies suggests that proactive and reactive balance strategies must be explored further, and outcome measures should reflect real-life circumstances when evaluating falls. 13 Additionally, balance confidence will influence how an individual approaches challenging environments, fall frequency, and their overall participation. 14 Therefore, assessments that evaluate functional performance and behaviors in a realworld environment will better elucidate the impact of their impairments.…”
mentioning
confidence: 99%
“…Typical signs of the disease are foot-drop, horse-like or toe-heel gait, ankle instability, postural instability, and increased risk of falls. 2,3 CMT also includes a sensorial (proprioceptive) deficit of the lower and upper limbs and symptoms such as cramps, asthenia, and neuropathic pain. 4 The disease is degenerative and usually shows a slow progression, involving the hands and the respiratory functions, consequently decreasing the patient's quality of life significantly.…”
Section: Introductionmentioning
confidence: 99%